The Aesthetic and Narrative Strategies of Subcultures on TikTok: Analyzing the Presentation of Niche Identities - Apichai T. Suriyapong (Studies in Social Science & Humanities, 2024)
This paper explores the aesthetic and narrative strategies employed by subcultures on TikTok to present and cultivate niche identities in a digital age characterized by rapid content consumption and algorithm-driven engagement. TikTok’s unique format—short, looping videos coupled with a powerful recommendation algorithm—has facilitated the rise and proliferation of diverse subcultural communities, such as cottagecore, dark academia, and witchtok. These groups leverage distinct visual styles, soundscapes, and narrative techniques to construct cohesive subcultural identities that resonate with both creators and viewers. Aesthetics serve as visual markers that communicate values and philosophies, while soundscapes and music act as auditory signifiers that further define the emotional and cultural landscapes of these communities. The platform’s algorithmic curation significantly influences the visibility, evolution, and dynamics of subcultural communities by promoting content that aligns with user engagement patterns.